E-028 Implementation of an ED-based Rapid Brain-Attack Triage Algorithm in a Regional Tele-stroke Network Positively Impacts Discharge Disposition for Stroke Patients. (26th July 2014) - Venizelos, A; Roper, D; Coulson, J; Patel, K; Myers, J; Fanale, C; Robbins, S; Janardhan, V
Abstract : Introduction: Implementation of standardized algorithms and EMS transport to centers with catheter-based capabilities have impacted time-to-treatment and functional outcomes in ischemic cardiac patients. However, there are limited data on the impact of triage algorithms and immediate access to centers with neurointerventional capabilities in the care of ischemic stroke patients. Hypothesis: A simplified algorithm for evaluating and triaging brain-attack patients in the emergency department (ED) of hospitals similar to heart-attack patients can improve discharge disposition. Methods: A Rapid Brain-Attack Triage Algorithm was implemented in the ED's within a regional stroke network. Ischemic and hemorrhagic stroke inpatient discharge diagnoses (ICD-9 codes) were analyzed prior-to (2010) and following (2012) the launch of ED-based Rapid Brain-Attack Triage Algorithm within the regional Tele-stroke network. The discharge dispositions were also analyzed. Patients were considered to have a "good" discharge disposition when they were discharged to home with self care, home with home health, or to an inpatient rehabilitation facility. Data were analyzed using the X 2 test for significance. Results: There were 2, 962 patients admitted with a principal diagnosis of stroke (either ischemic or hemorrhagic) in 2010 and 68% had a "good" discharge disposition (2000/2962) (Figure-top). In comparison, there were 76% of stroke patients (3428/4538) who had a "good" discharge disposition in 2012 (Figure-bottom). This 12% improvement in "good" outcomes following the launch of ED-based Rapid Brain-Attack Triage Algorithm within a regional Tele-stroke network was statistically significant (X 2 = 58; p < 0.001). Conclusions: A simplified ED-based Rapid Brain-Attack Triage Algorithm and triage of appropriate patients to comprehensive stroke centers for consideration of catheter-based therapy is feasible and significantly improves discharge disposition in stroke patients. Disclosures: A. Venizelos: None. D. Roper: None. J. Coulson: None. K. Patel: None. J. Myers: None. C. Fanale: None. S. Robbins: None. V. Janardhan: None.